SOFIA - Opitcal Operating System and Medical Analyses (Global Journals of Research in Engineering, 2020)
Nursing is an area of extreme relevance to society It is an area that requires intense psychological due to excessive working hours However the accumulation of patients added to the exhaustion of the routine causes many nurses to face psychological problems such as the Burnout syndrome The assistance becomes impaired through a cascade effect This set of questions ends up generating a considerable delay in attendance causing the hospital queues to increase which in turn causes an aggravation of the patients diseases The care of the elderly and children especially children with down syndrome or autism is more complicated and without attention can make these people feel uncomfortable stressed or even enter into a panic The SOFIA project Optical System of Operation and Medical Analysis aims to provide public hospitals and other similar places with an electronic system that can perform a screening process more quickly effectively and non-invasively and monitoring the patients if necessary
Keywords: effective; clinical exams; totem robot